REALISATION AND EXPERIMENTATION OF A WIND TOWER FOR PASSIVE EVAPORATIVE COOLING IN HOT DRY AREA: HASSI MESSAOUD, ALGERIA - Djouima, A.; Bouchahm, Y.; Bourbia, F.; Torkia, A. (University of Eloued جامعة الوادي, 2018)
The wind tower is one of the solutions to overheating issues. Using them in Algeria would be a solution in cooling hot areas and reducing energy consumption and greenhouse gas emissions. This research aims to develop a passive alternative to active cooling by exploring potentials and design parameters of wind catchers. The configuration of this built tower was based on a modified version of a model by Bouchahm (2011). The methodology used to this end consists of experimentally exploring the efficiency of wind towers through direct heat transfer induced by humidification of its built columns. Experiments on cooling efficiency were performed. The temperature and relative air humidity were monitored from May to August 2007 with and without humidification of the tower columns. The results are comparable to those of the simulated model. Lower temperatures were also recorded.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Summer thermal comfort; passive evaporative cooling; humidified column; hot and arid climate; wind towers.